INCORPORATING A GENRE-BASED APPROACH IN TEACHING WRITING EXPOSITION ENGLISH TEXT - Arisandi, Vidya; Asmara, Andes Safarandes; Sudrajat, Ajat (TELL - US JOURNAL, 2023)
Lecturers can effectively teach students to write expository texts, specifically job application letters, using a genre-based approach. This instructional method enhances students' comprehension of text types, the schematic structure of the text, linguistic characteristics, and the social function associated with this text type. This study aims to investigate the application of the genre-based approach in teaching expository writing with a focus on job application letters. The research participants consist of management students at a private university in Karawang who are enrolled in English for business management. The research design adopts a descriptive qualitative approach, incorporating observation of the exposition text learning process with a job application letter, interviews to appraise students' perceptions, and analysis of documentation, specifically the students' writing samples. The findings and subsequent discussion reveal the lecturer's commitment to effectively implementing each stage of the genre-based approach in teaching expository writing. The lecture demonstrates meticulous planning by developing a syllabus, lesson plans, and targeted instructional strategies. Additionally, the interview data indicates that students require sufficient time and guidance to master the writing of job application letters within the context of expository texts. However, the students ultimately display proficient writing skills in composing well-structured expository texts in English. Furthermore, the analysis of the documentation, comprising the students' writing samples, corroborates the successful outcomes of the job application letter compositions, which were achieved through iterative feedback provided by the lecturer. In conclusion, this research highlights the lecturer's successful implementation of the genre-based approach in student learning.